ZM336372 Induces Apoptosis Associated With Phosphorylation of GSK-3β in Pancreatic Adenocarcinoma Cell Lines - Deming, Dustin (2009)
INTRODUCTION: ZM336372 is small molecule tyrosine kinase modulator. It has been shown to inhibit glycogen synthase kinase-3β (GSK-3β) through phosphorylation of GSK-3β at Ser 9. GSK-3β has previously been shown to mediate cell survival in pancreatic cancer cells. Here we determine the effects of ZM336372 on GSK-3β phosphorylation, apoptosis, and growth in pancreatic adenocarcinoma cell lines. METHODS: Panc-1 and MiaPaCa-2 cells were treated with ZM336372 or lithium chloride (LiCl) and compared to solvent control. The effects on proliferation for each cell line were determined using the MTT assay. Western blot analysis was performed to examine the effects of treatment on the phosphorylation of GSK-3β. In addition, western blot was utilized to examine the cleavage of PARP, a marker of apoptosis. RESULTS: A dose-dependent increase in phosphorylation of GSK-3β was observed after treatment with both ZM336372 and LiCl. Growth inhibition due to treatment with ZM336372 and LiCl also occurred in a dose-dependent fashion. An increase in cleaved PARP was demonstrated after treatment with both agents, as was seen previously with GSK-3β inhibition in pancreatic adenocarcinoma cells. CONCLUSION: This is the first description of growth inhibition and apoptosis in pancreatic cancer cells related to GSK-3β inhibition through treatment with ZM336372.